Macrophage Depletion Protects against Cigarette Smoke-Induced Inflammatory Response in the Mouse Colon and Lung - Lim, Dahae; Kim, Woogyeong; Lee, Chanju; Bae, Hyunsu; Kim, Jinju (Frontiers in Physiology, 2018)
Cigarette smoke (CS) is considered to be a major possible risk factor for pulmonary and intestinal inflammation. CS causes macrophages recruitment into the mucosa of both organs, and these cells promote inflammatory response by inducing uncontrolled secretion of inflammatory mediators, including cytokines, chemokine, and MMPs. In this study, we investigated whether macrophage depletion modulates the cigarette smoke (CS)-induced inflammatory response in both the lung and bowel. The mice were exposed to CS for 30 min, after which they were rested in a fresh air environment for 30 min. The total duration of exposure to CS was 2h per day for 4 weeks. Macrophage depletion state was made by injection of clodronate containing liposome. Individual body weights were measured twice a week, and the mice were sacrificed on day 28. Hematoxylin and eosin (H&E) staining was performed in the lung and colon tissue to determine histological changes. Inflammatory mediators’ synthesis was analyzed using ELISA and western blotting. Clodronate liposome treatment ameliorated pathological changes with infiltration of immune cells in the lung and colon. Also, clodronate liposome injected mice showed significantly lower levels of inflammatory mediators, including cytokines and chemokine, proteases as well as NF-κB. Our results indicated that macrophage depletion by clodronate liposome treatment attenuates the CS-induced inflammatory response in both the lung and colon.